Hemoglobin mass and peak oxygen uptake in untrained and trained female altitude residents - Bönning, D.; Cristancho, E.; Serrato, M.; Reyes, O.; Mora, M.; Coy, L.; Rojas, J. (International Journal of Sports Medicine, 2004)
Total hemoglobin mass has not been systematically investigated in females at altitude. We measured this quantity (CO-rebreathing method) as well as peak oxygen uptake in 54 young women (age 22.5 , 0.6 SE years) with differing physical fitness living in Bogot? (2600 m) and compared the results with those of 19 subjects from 964 m in Colombia and 75 subjects from 35 m in Germany. In spite of an increased hemoglobin concentration the hemoglobin mass was not changed in highlanders (means 9.0 to 9.5 g / kg-1 in untrained subjects at all altitude levels). Endurance trained athletes, however, showed a rise in hemoglobin mass by 2 - 3 g / kg-1 at all sites. Erythropoietin was little increased in Bogota; iron stores were within the normal range. Aerobic performance capacity was lower at high altitude than at sea level and remained so also after correction for the hypoxic deterioration in untrained and moderately trained subjects but not in athletes; possibly the cause was reduced daily physical activity in non-athletic Bogotanians compared to lowlanders. After exclusion of the factor VO2peak by analysis of covariance a mean rise of 6.6 % in hemoglobin mass at 2600 m was calculated being smaller than in males (> 12 %). The attenuated increase of hemoglobin mass in female highlanders possibly results from stimulation of ventilation improving arterial oxygen saturation or from an increased hypoxia tolerance of cellular metabolism both caused by female sexual hormones.